Surveying and Mapping in Southern Peary Land, North Greenland. - Høy, Thorkild (Meddelelser om Grønland, 1970)
The present paper is first of all of a cartographical character, as the text must be viewed in close connexion with the maps appended and forms the background of the procurement of these under expeditionary conditions as regards the field work. Furthermore, the text is to form the basis of an evaluation of the accuracy and completeness of the graphical information offered by the maps. Finally the work should be viewed as an attempt at improving and sharpening the sense of the map as a scientific implement and at providing an exacter foundation of it as an implement. Results of a hydrological character are communicated: accumulation /ablation measurements on Chr. Erichsens Iskappe made partly on staffs, partly through levellings made in 1949, 1950, and 1963, and - in an appendix- measurements of run-off in the Kedelkrogelv. The connexion of the run-off with the temperature of the air and the relative independence of the precipitation of the individual years are demonstrated.